Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1155/2015/867293
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 Inhibits the Aging of Mesenchymal Stem Cells Induced by D-Galactose through Akt/mTOR Signaling

Abstract: Increasing evidences indicate that reactive oxygen species are the main factor promoting stem cell aging. Recent studies have demonstrated that coenzyme Q10 (CoQ10) plays a positive role in organ and cellular aging. However, the potential for CoQ10 to protect stem cell aging has not been fully evaluated, and the mechanisms of cell senescence inhibited by CoQ10 are still poorly understood. Our previous study had indicated that D-galactose (D-gal) can remarkably induce mesenchymal stem cell (MSC) aging through p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 66 publications
5
44
0
1
Order By: Relevance
“…We observed that the significant inhibitory effects on platelet function range between the concentrations of 10 and 100 µM (the highest concentration tested). These findings are consistent with other in vitro studies . However, after 24 weeks of supplementation, the plasma CoQ10 concentration in dyslipidemic patients was ≈2 µM (Figure S6, Supporting Information), at this concentration the platelet aggregation in healthy human gel‐filtered platelets was not significantly inhibited, when CoQ10 was added in vitro (Figure S10, Supporting Information).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We observed that the significant inhibitory effects on platelet function range between the concentrations of 10 and 100 µM (the highest concentration tested). These findings are consistent with other in vitro studies . However, after 24 weeks of supplementation, the plasma CoQ10 concentration in dyslipidemic patients was ≈2 µM (Figure S6, Supporting Information), at this concentration the platelet aggregation in healthy human gel‐filtered platelets was not significantly inhibited, when CoQ10 was added in vitro (Figure S10, Supporting Information).…”
Section: Discussionsupporting
confidence: 90%
“…For the in vitro study, concentrations of CoQ10 (1, 10, 100 µM) used were consistent with previous studies . These doses did not exert cytotoxic effects on platelets as measured by lactate dehydrogenase (LDH) leakage from platelets (Figure S1, Supporting Information).…”
Section: Methodssupporting
confidence: 77%
“…As shown in previous studies on tissues or cells from other organs, Q10 treatment on doxorubicin challenged SD resulted in regulation of pro-apoptotic proteins and thereby inhibited apoptosis, Q10 also increased survival protein expression to enhances cell survival by acting as an effective antioxidant (Chen et al, 2011;Navas et al, 2002;Zhang et al, 2015).…”
Section: Discussionsupporting
confidence: 62%
“…Recent studies have linked activation of the Akt and mTOR signaling pathways with the production of ROS and altered cell viability [31]. As shown in Figure 6, cells grown in galactose exhibited increased Akt and mTOR phosphorylation as compared to glucose-grown cells.…”
Section: Glucose Oxidation and Protection Against Ischemia-reperfusiomentioning
confidence: 94%